Sugar, Soil and Sequencing: Studies in Fusarium venenatum - Whittaker, Jack Alexander (2022)
Studies were undertaken to gain insights into the biology and genetics of the industrial microorganism Fusarium venenatum with the aim of improving biotechnological aspects of the Quorn™ mycoprotein industrial process. This was addressed first by exploring previously unexamined biodiversity in the species and second by trialling alternatives to the current high-cost glucose feedstock. Since it’s discovery in the 1960s only a single isolate, F. venenatum A3/5. had been implemented in the Quorn™ industrial process. Initial work involved establishing an isolate collection of F. venenatum with the aim of identifying isolates that might show improvements in biotechnologically relevant parameters compared to A3/5. Surveys of global culture collections and research contacts yielded 24 strains. Archival research at Quorn Foods revealed that several of these strains were not unique but instead A3/5-derived mutants. In parallel, environmental sampling was undertaken using Fusarium spp. selective media. Samples were collected from a variety of locations across the U.K. including the original site of isolation of A3/5. Work included development of an F. venenatum-specific PCR-based molecular diagnostic. Despite these efforts, no isolates of F. venenatum were retrieved, indicating that the species is relatively rare rather than being a ubiquitous soil microorganism as originally thought. The genomes of 21 putative F. venenatum strains from the isolate collection were sequenced and assembled for use in comparative genomics. This provided insights into the potential for sexual reproduction in F. venenatum. Before this work, only A3/5 had been genome sequenced and shown to be of MAT1-1 mating type. Using molecular and bioinformatic analysis, four MAT1-2 strains were identified and the first structural description of the F. venenatum MAT1-2 locus is provided. This work provides a foundation for future work aimed at using the sexual cycle for strain improvement of F. venenatum and also provides a valuable resource for future F. venenatum research, both industrial and academic, such as genome analysis of mycotoxin production. The second aim of this thesis was to characterise F. venenatum growth on alternative carbon substrates, with the goal of identifying an alternative(s) to the current high-cost glucose syrup feedstock. A high-throughput optical density-based system was developed for rapid screening of growth on potential candidate substrates. F. venenatum A3/5 was shown to exhibit metabolic flexibility, with growth supported by a variety of sugars including D-xylose, D-galactose and lactose. It was also shown that low-cost substrates such as high-fructose syrups and lignocellulosic breakdown products were also effective carbon substrates for F. venenatum. Sucrose was identified as the most suitable replacement feedstock, supporting A3/5 growth rates of equal magnitude to glucose. Alternative strains of F. venenatum from the isolate collection were also screened for growth on glucose and sucrose, but no significant differences in growth were evident from A3/5. Further studies were made of the effect of sucrose on additional characteristics such as germination, substrate utilisation and mycotoxin biosynthesis using both small-scale and larger 5 L and 10 L batch or steady-state fermentations. Sucrose had previously been identified as a potent inducer of mycotoxin biosynthesis in the fusaria, with production of the Type A trichothecene, diacetoxyscirpenol (DAS) previously reported in F. venenatum. Therefore, investigations were made into the effect of the use of glucose and sucrose as feedstocks on mycotoxigenesis in A3/5 and the 24 alternative F. venenatum strains. A considerable strain-specific effect on DAS production was observed, with most strains presenting increased DAS biosynthesis at the stationary phase when supplied with sucrose as compared to glucose. However, a number of strains demonstrated lower levels of DAS biosynthesis compared to A3/5, suggesting that these might be potential industrial replacements. Of particular significance was the discovery of a putative non-DAS producing strain 114-23, which failed to synthesise DAS when fed glucose or sucrose. This strain when used in combination with sucrose may provide a worthy successor to the A3/5 and glucose paradigm currently established at Quorn™.